Pengaruh Harga, Kualitas Produk Dan Lokasi Terhadap Minat Beli Konsumen Rumah Makan Ganto Minang Jakarta - Shobur, Achmad; Kanto, Dwi Sunu; Alananto, Donant (STREAMING, 2023)
Marketing activities are carried out for profit. This activity must be carried out on target. When buying an item, consumers will consider several factors including product quality, price, and location. Consumer purchase intention is the stage where consumers form their choices among several brands that are incorporated in the choice set, then in the end make a purchase at an alternative that they like the most or the process that consumers go through to buy an item or service based on various considerations. This study aims to determine the effect of price, product quality, and location on consumer purchase intention. A sample of 156 people are consumers of the Ganto Minang Restaurant in Jakarta. This quantitative descriptive study was analyzed with multiple regression. The results of the study show that price, product quality, and location have a significant effect on consumer purchase intention either partially or simultaneously.